Study of the genre of poetry in linguistic works (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The works of scientists who studied the genre of poetry in linguistics are described. The language of poetry is analyzed, the stylistic features of poetry, positive and negative aspects are analyzed, and a conclusion is drawn. The main systematic structures of linguopoetics and their use in a work of art are listed.
Keywords: кyrgyz poetry, poetic work, lyrics, genre poetry, poetic linguistics, poetic language, rhyme, synharmony, language of poetry